A Standardized Approach to Cesarean Surgical Technique and Its Effect on Operative Time and Surgical Morbidity - Pallister, M.; Ballas, J.; Kohn, J.; Eppes, C. S.; Belfort, M.; Davidson, C. (American Journal of Perinatology, 2019)
Objective To evaluate the impact of a standardized surgical technique for primary cesarean deliveries (CDs) on operative time and surgical morbidity.Materials and Methods Two-year retrospective chart review of primary CD performed around the implementation of a standardized CD surgical technique. The primary outcome was total operative time (TOT). Secondary outcomes included incision-to-delivery time (ITDT), surgical site infection, blood loss, and maternal and fetal injuries.Results When comparing pre- versus postimplementation surgical times, there was no significant difference in TOT (76.5 vs. 75.9 minutes, respectively; p = 0.42) or ITDT (9.8 vs. 8.8 minutes, respectively; p = 0.06) when the entire cohort was analyzed. Subgroup analysis of CD performed early versus late in an academic year among the pre- and postimplementation groups showed no significant difference in TOT (79.3 early vs. 73.8 minutes late; p = 0.10) or ITDT (10.8 early vs. 8.8 minutes late; p = 0.06) within the preimplementation group. In the postimplementation group, however, there was significant decrease in TOT (80.5 early vs. 71.3 minutes late; p = 0.02) and ITDT (10.6 early vs. 6.8 minutes late; p < 0.01). Secondary outcomes were similar for both groups.Conclusion A standardized surgical technique combined with surgical experience can decrease TOT and ITDT in primary CD without increasing maternal morbidity.
Keywords: standardized surgical technique; primary cesarean delivery; total operative time; incision-to-delivery time